Effectiveness of Computer-Based Nursing Documentation in Nursing Care in Hospital - A literature Review - Brajakson Siokal (Journal of Muslim Community Health, 2021)
Background: Nurse Population in hospitals has a greater proportion than other health workers. Nearly 60-70% of the total human resources available, occupied by nurses. In fact, 90% of the health services provided are a form of nursing service. Therefore, nursing service is a form of professional service that is the biggest indicator in realizing the quality of hospital services. One of the duties of nurses in providing nursing services in accordance with standards is to document all nursing care provided. Objective: To review journals about documenting computer-based nursing care in hospitals for the effectiveness of the preparation of nursing care. Methods: Quantitative, mixed-methods, and qualitative reviews that aim to evaluate the influence of computerized nursing documentation (eg, management, computerized decision support systems and information systems) on nursing care were included. We used the nursing care performance framework as an extraction grid and analytical tool. This model illustrates how the interplay between nursing resources and nursing services can produce changes in patient conditions. The primary outcomes included nurses' practice environment, nursing processes, professional satisfaction, and nursing-sensitive outcomes. The secondary outcomes included satisfaction or dissatisfaction with computerized nursing documentation according to nurses 'and patients' perspectives. Reviews published in English, French, or Spanish from January 1, 2000 to December 15, 2019, were considered. Results: A total of 5515 titles or abstracts were assessed for eligibility and full-text papers of 72 articles were retrieved for detailed evaluation. It was found that 22 reviews published between 2002 and 2015 met the eligibility criteria. Many nursing care themes (ie, indicators) were influenced by the use of computerized nursing documentation, including time management; time spent on patient care; documentation time; information quality and access; quality of documentation; knowledge updating and utilization; nurse autonomy; intra and interprofessional collaboration; nurses' competencies and skills; nurse-patient relationship; assessment, care planning, and evaluation; teaching of patients and families; communication and care coordination; perspectives of the quality of care provided; nurses and patients satisfaction or dissatisfaction with computerized nursing documentation; patient comfort and quality of life related to care; empowerment; and functional status.